Analisis Tren Konsumsi Energi Listrik pada Penyulang Singkarak - Erliza Yuniarti; Dian Tara; Andika Pratama; Deni Rahmadi Putra (Fakultas Teknik, 2021)
Electrical energy use is an interesting topic because it is related to the operational planning of the distribution system, maintenance of medium voltage networks, and prediction of electricity consumption, especially in the short term. Trends are created based on historical data represented in the load curves. This research aims to determine the characteristics of the load by making load groups according to the type of day and calculate the load factor based on secondary data from PT. PLN (Persero) Borang substation. The research uses comparative techniques in the load groups and calculates the load factor which is the benchmark for generation capacity. The results of the study showed that the load trendon Singkarak feeders in overall is the same on weekdays as on weekends, namely that minimum load occurs in the morning at 07.00, the load starts to increase but is not significant in relation to the activities of the population after 08.00-16.00. The load trend increases significantly from 16.00 to the peak load that occurs at 19.00-21.00 and after that, the load goes down to the minimum load. The trend for higher than average peak loads on Mondays is more common and weekend loads on Saturdays and Sundays only relatively small load fluctuationsoccur.. The load group for religious holidays and national holidays received good load factor scores, with a relatively small range of loads throughout the day.